Aggregate And Fill Source Study Of West Qurna And Adjacent Area, Southern Iraq - Hany, Hamid Doshan (University of Thi-Qar Journal of Science, 2019)
The area of west Qurna oil fields is a low topography and represent a part of the marshes dried. The top layer of soil is composed of cohesive fragile with compression is very low. The thickness of its is about 1m, rich in organic matter. This soil is not suitable to establishing pads for oil wells, up appropriately and establish a road network connecting these wells with each other and with the main roads in the region.The soil sections were tested visually. The coordinates and photographs of mentioned sections were took using GPS and digital camera respectively. Improved raw satellite image were used which captured by Landsat in April 5th , 2003 covering "path 166 raw 39" . ERDAS and ARC GIS, software version ninth were used to preparation the satellite image for serves the purpose of the study, produced the land cover land use digital map, and to locate the visited sites on this map.It has been confirmed that the Onsite of west Qurna area is empty from any source of aggregate, because the sections of the soil is:- From top to 12m deep is silt clay, marely clay and organic clay. From 12m to 17m is silt sand. From 17m to 20m is sand. Deeper than 20m is sand stone. The water table is about 6m.In the other hand the granular sand cover a very wide area of the southern part of study area (Offsite) which adjacent to west Qurna area. Another part covered with new sediments of the Gypcrete alluvial fan. The percentage of the sand increased as the gravels decrease from south- west to north-east. The gravels have different size, the smaller is granule, and the bigger like cobble as maximum. There are about 30 out crops utilized as aggregate quarries for construction. They are about 5-12 m deep. Their sediments are layer type. Sometimes, the sediments lens type are parallel or semi parallel, positioned among other layers. Lithological column consist of number of consecutive sediment cycles of basin cross plane bedding become gradually more fine as it directs upward. The thickness of the sediment cycles is about (5-2m). The ground water level locates at depth more than 15m.